Non-bank investors and loan renegotiations - Teodora Paligorova; Jo\~ao A. C. Santos (Bank of Canada, 2016)
We document that the structure of syndicates affects loan renegotiations. Lead banks with large retained shares have positive effects on renegotiations. In contrast, more diverse syndicates deter renegotiations, but only for credit lines. The former result can be explained with coordination theories. The puzzling effect of syndicate diversity in term loan renegotiations derives from the growth of collateralized loan obligations (CLOs) in the syndicated loan market and the coordination between these vehicles and lead banks. CLOs that have a relationship with the lead bank of the renegotiated loan are strong supporters of amount-increase renegotiations, arguably because this gives them access to attractive investments. Related CLOs fund not only their portion of the loan increase, but also the portion that was supposed to be funded by the lead bank. Our findings highlight the previously unrecognized role of the growing presence of non-bank lenders in corporate lending.
Keywords: G21; G23; 330; Financial institutions; Financial system regulation and policies